Comparative application of IS711-based polymerase chain reaction (PCR) and loop-mediated isothermal amplification (LAMP) for canine brucellosis diagnosis. (June 2018) - Batinga, Maria Cryskely Agra; de Lima, Julia Teresa Ribeiro; Gregori, Fabio; Diniz, Jaqueline Assumpção; Muner, Kerstin; Oliveira, Trícia M.F.S.; Ferreira, Helena Lage; Soares, Rodrigo Martins; Keid, Lara Borges
Abstract: Canine brucellosis is caused by Brucella canis, a gram negative and facultative intracellular bacterium that is commonly associated with reproductive failures in dogs. The accurate diagnosis of the infection relies on the use of serological tests associated with blood culturing to guarantee sensitivity. The polymerase chain reaction (PCR) can replace the culturing procedure for the direct diagnosis of the infection because of its speed, high specificity and sensitivity values; however, it depends on some laboratory infrastructure to be conducted. The loop-mediated isothermal amplification (LAMP) may be an alternative method for DNA amplification in a shorter period, using simpler equipment, and with a lower cost. This study evaluated the potential of molecular tools based on PCR and LAMP using primers targeting the insertion sequence IS711 for Brucella detection in three groups of dogs (infected, non-infected and suspected of brucellosis), which were determined according to the results of blood culturing and clinical examination. The performance of the three diagnostic tests was also determined using McNemar test and Kappa coefficient. The proportion of positive samples detected by blood culturing, PCR and LAMP was respectively 31.57% (18/57), 33.34% (19/57), and 14.03% (8/57). The agreement between blood culturing and PCR was almost perfect, while the agreement of PCR and blood culturing compared to LAMP was fair. The diagnostic sensitivity of PCR and LAMP was respectively 100% (18/18) and 44.44% (8/18), while the diagnostic specificity of both tests was 100% (21/21). LAMP performance was not satisfactory for canine brucellosis diagnosis because of the low diagnostic sensitivity of the test. The IS711 based PCR, otherwise, showed high values of sensitivity and specificity, which makes it a good alternative for use for the rapid diagnosis of canine brucellosis. Highlights: IS711-based PCR showed high diagnostic sensitivity and specificity for Brucella canis detection in canine blood. IS711-based LAMP showed a low diagnostic sensitivity for canine brucellosis diagnosis. The regular update of primers is a mandatory measure to ensure a high performance of the molecular diagnosis.